2013
DOI: 10.1146/annurev-arplant-050312-120106
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Functions of the Bacterial Microbiota of Plants

Abstract: Plants host distinct bacterial communities on and inside various plant organs, of which those associated with roots and the leaf surface are best characterized. The phylogenetic composition of these communities is defined by relatively few bacterial phyla, including Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria. A synthesis of available data suggests a two-step selection process by which the bacterial microbiota of roots is differentiated from the surrounding soil biome. Rhizodeposition appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

105
2,053
2
48

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,627 publications
(2,208 citation statements)
references
References 153 publications
105
2,053
2
48
Order By: Relevance
“…Endophytes have been found to be closely related to human pathogens or opportunistic human pathoges [51], which could trigger potential threat to human health. Phyllosphere, normally referring to the aerial leaf surfaces, is a special niche harboring diverse species of microbes, especially bacteria [52]. Therefore, vegetables grown in manureamended soil, particularly that are eaten raw or only subjected to minimal processing before consumption, could serve as vehicles for expanding the pool of antibiotic resistance available to bacteria (pathogens or otherwise) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes have been found to be closely related to human pathogens or opportunistic human pathoges [51], which could trigger potential threat to human health. Phyllosphere, normally referring to the aerial leaf surfaces, is a special niche harboring diverse species of microbes, especially bacteria [52]. Therefore, vegetables grown in manureamended soil, particularly that are eaten raw or only subjected to minimal processing before consumption, could serve as vehicles for expanding the pool of antibiotic resistance available to bacteria (pathogens or otherwise) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Community assembly processes could be divided into four main forces: dispersal, diversification, ecological drift and selection (Nemergut et al 2013). Recently, many research groups have investigated the importance of selection in determining community assembly in the rhizosphere and the phyllosphere (Bulgarelli et al 2013;Müller et al, 2016). For instance, it has been shown that selection by the environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is significant evidence to suggest that ecological functions performed by the phytomicrobiome extend a plant's ability to adapt to different environmental conditions and changes (Bulgarelli et al ., 2013), which is of primary significance for the plant's fitness considering their sessile lifestyles. However, traditional crop breeding programmes do not consider key components of crop fitness, i.e.…”
Section: Rhizosphere Versus Phytomicrobiome Approachesmentioning
confidence: 99%